White collar radicals : TVA's Knoxville Fifteen, the New Deal, and the McCarthy era - Purcell, Aaron D., 1972- (University of Tennessee Press, 2009)
They came from all corners of the country--fifteen young, idealistic, educated men and women drawn to Knoxville, Tennessee, to work for the Tennessee Valley Authority, one of the first of President Franklin D. Roosevelt's New Deal projects. Mostly holding entry-level jobs, these young people became friends and lovers, connecting to one another at work and through other social and political networks. What the fifteen failed to realize was that these activities--union organizing and, for most, membership in the Communist Party--would plunge them into a maelstrom that would endanger, and for some, destroy their livelihoods, social standing, and careers. White Collar Radicals follows their lives from New Deal activism in the 1930s through the 1940s and 1950s government investigations into what were perceived as subversive deeds. Aaron D. Purcell shows how this small group of TVA idealists was unwillingly thrust from obscurity into the national spotlight, victims and participants of the second Red Scare in the years after World War II. The author brings into sharp focus the determination of the government to target and expose alleged radicals of the 1930s during the early Cold War period. The book also demonstrates how the national hysteria affected individual lives. White Collar Radicals is both a historical study and a cautionary tale. The Knoxville Fifteen, who endured the dark days of the McCarthy Era, now have their story told for the first time--a story that offers modern-day lessons on freedom, civil liberties, and the authority of the government.